Squaraine-Doped Functional Nanoprobes: Lipophilically Protected Near-Infrared Fluorescence for Bioimaging - Lee, Yong-Deok; Lim, Chang-Keun; Kim, Sehoon; Kwon, Ick Chan; Kim, Jungahn (WILEY-BLACKWELL, 2010)
Hydrophobically stabilized near-IR fluorescence from self-assembled nanoprobes composed of amphiphilic poly(maleic anhydride-alt-octadec-1-ene) (PMAO) and lipophilized squaraine dopants is reported. From comparative studies with varying lipophilicity of squaraine dyes as well as of nanoparticulate polymer matrices, it is found that dual protection by simultaneous lipophilization of the dye-polymer pair greatly improves the chemical stability of labile squaraine dyes, to produce efficient NIR fluorescence in physiological aqueous milieux. The surface properties of negatively charged PMAO nanoparticles are readily modified by coating with an amine-rich cationic glycol chitosan with biofunctionality. Efficient cellular imaging and in vivo sentinel lymph node mapping with size and surface-controlled nanoprobes demonstrate that lipophilic dual protection of NIR fluorescence and the underlying functional nanoprobe approach hold great potential for bioimaging applications.
Keywords: IR DYES; NANOPARTICLES; NANOCRYSTALS; ROTAXANES; ENCAPSULATION; CHEMISTRY; SYSTEMS; PROBES; DRUGS